Seasonal Occurrence of Western Flower Thrips, Frankliniella occidentalis (Pergande), on Table Grapes in the Hex River Valley, South Africa - Allsopp, E. (South African Journal of Enology and Viticulture, 2016)
Western flower thrips (WFT), Frankliniella occidentalis (Pergande), on table grapes in the Hex River Valley was monitored and its seasonal occurrence was investigated over three seasons. At the start of the growing season, blue sticky traps suspended from the overhead trellising structure to hang outside and under the vine canopy yielded similar WFT numbers. However, as the season progressed and vine canopies became denser, more WFT were caught on traps hanging outside the canopy in full sunlight than on traps hanging under the vine canopy. Female WFT became active in the vineyards after bud break and their numbers increased rapidly during flowering, peaking between October and January and declining rapidly thereafter. WFT were present in pre-bloom inflorescences and shoot tips before flowering, which means that monitoring should commence as soon as the first inflorescences are formed. No consistent relationship was found between economic damage at harvest and WFT numbers on sticky traps during flowering and berry set. Sticky traps should therefore only be used to determine the presence or absence of WFT in vineyards. The trap results suggest that there could be a constant influx of thrips into vineyards from alternate host plants in the surrounding area during the growing season. In vineyards with a history of WFT damage, control measures should be considered as soon as WFT is detected in order to prevent halo spot damage.